2021
DOI: 10.1136/thoraxjnl-2021-217981
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of hygiene, face covering and social distancing interventions to prevent exacerbations in people living with airways diseases

Abstract: Interventions to prevent the spread of SARS-CoV-2 have been associated with substantial reductions in exacerbations of airways diseases, likely through reduced transmission of other respiratory viruses. We surveyed 4442 people with airways disease (asthma=3627, bronchiectasis=258, chronic obstructive pulmonary disease=557) to gauge attitudes and intentions towards continuing such measures after the COVID-19 pandemic. 47% intended to continue wearing a face mask in indoor public spaces, and 61% thought everyone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…Their support for future policy initiatives was also strong, as shown by their support for 77% of the proposed measures. This supports an earlier study by Hurst et al (2021), which showed that a significant number of people living with chronic lung disease believed that anti-infection measures should be applied to the wider community as well as to themselves beyond the COIVD-19 pandemic, particularly during the flu season [18]. For the future implementation of such measures among smokers and people living with chronic lung disease, special consideration should be paid to the benefits and potential harms of these measures, including cost and psychological harm [18,30].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Their support for future policy initiatives was also strong, as shown by their support for 77% of the proposed measures. This supports an earlier study by Hurst et al (2021), which showed that a significant number of people living with chronic lung disease believed that anti-infection measures should be applied to the wider community as well as to themselves beyond the COIVD-19 pandemic, particularly during the flu season [18]. For the future implementation of such measures among smokers and people living with chronic lung disease, special consideration should be paid to the benefits and potential harms of these measures, including cost and psychological harm [18,30].…”
Section: Discussionsupporting
confidence: 93%
“…This research used a modified version of a previously validated assessment survey [ 18 ]. The survey is adaptive and consists of three sections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such relevant information can be shared through apps with COPD patients engaged in their own self-management owing to frequent exacerbations of their disease [16]. A patient's knowledge of at-risk environmental situations will enable them to make informed choices and modify their own risk of exacerbation by limiting social interactions, avoiding polluted areas, and asking family members to prudently wear masks in case of infection symptoms [17]. There are many smartphone applications now providing information regarding actual indices of air quality with appropriate spatial and temporal granularities.…”
Section: Assessment Of External Factorsmentioning
confidence: 99%